Adopsi pola sustainable consumption awareness sebagai realisasi ekologi integral bagi our common home dalam perbedaan perspektif antar generasi - Pranatasari, Fransisca Desiana; Kristanto, Agustinus Tri; Wardhani, Aurelia Melinda Nisita; Kurniawati, Lucia; Adinata, Patrick Vivid (Universitas Widya Mataram, 2024)
Global warming issue, attracts collective attention because it is detrimental to human life in the future. This has a huge impact on future generations. Therefore, there is a need for public awareness of sustainable consumption patterns or responsible consumption. Adoption of sustainable products can have a positive impact on future generations in various aspects, especially in the scope of integral ecology, namely the earth as our common home. Decision-making regarding consumption patterns needs to be explored more deeply in relation to awareness of sustainable consumption between generations and needs to look at differences in perceptions between generations. The respondents used in this research were the baby boomer generation, X, Y, and Z. Quantitative research using the survey method was carried out by distributing questionnaires. The analysis technique was carried out using non-parametric statistical tests with Kruskal Wallis. The results of this research show that there are differences in the perception of sustainable consumption awareness in the baby boomer, X, Y, and Z generations.